Electron spin relaxation in CMR manganites: absence of critical acceleration - Atsarkin, V.A.; Demidov, V.V.; Simon, F.; Gaal, R.; Moritomo, Y.; Conder, K.; Jánossy, A.; Forró, L. (Journal of Magnetism and Magnetic Materials, 2003)
Using original modulation technique, the longitudinal electron spin-lattice relaxation time T 1 has been measured in a series of nearly cubic La 1− x Ca x MnO 3 ( x=0.1; 0.2; 0.25; 0.33) and layered La 2−2 x Sr 1+2 x Mn 2O 7 ( x=0.4 and 0.5) manganites both in paramagnetic state and around the temperature ( T c) of the magnetic ordering. The data are compared with the evolution of the transverse relaxation time T 2 as determined from the ESR linewidth. Well above T c, the T 1= T 2 equality is confirmed, whereas a pronounced slowing down of T 1 is observed in all the materials as T c is approached. The temperature dependence of T 1 is found to be consistent with that of Tχ( T), where χ( T) represents the temperature dependence of the electron-spin susceptibility determined from the ESR absorption area. The interpretation suggests freezing the local field fluctuations due to polarization of superparamagnetic clusters in the external magnetic field.